ANALISIS PENGARUH KANAL PROMOSI MEDIA SOSIAL INSTAGRAM TERHADAP OMZET KEDAI CANDU COFFEE PANGKALPINANG - Chandra, Kevin; Manullang, Rizal Ruben; Zamhari (Jurnal Progresif Manajemen Bisnis, 2023)
This research was entitled: “Analisis Pengaruh Kanal Promosi Media Sosial Instagram Terhadap Omzet Kedai Coffee “Candu Coffee” Pangkalpinang”. The research method to be used is descriptive quantitative by distributing questionnaires to 100 respondents using the Simple Linear Regression technique. The results showed that the Instagram Social Media Promotion Channel has the ability to significantly influence coffee shop Sales Turnover with a P-value <0.001 and a Simple Linear Regression equation Y = 4.185 + 0.407 * X1.